2021
DOI: 10.1002/admi.202100452
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially Bridged Graphene Sheets for High‐Performance Anticorrosion

Abstract: Graphene has been widely studied in metal protection due to its complete impermeability and ultrathin properties. However, it is still a huge challenge to fully use the unparalleled features to design and construct graphene‐based coatings with long‐term anticorrosion properties. Herein, a facile and scalable approach to design an ultrathin bioinspired graphene‐based (B–G–WEP) composite coating through sequential bridging of interfacial interactions and ordered graphene layers, is described. The combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…As the structural analogue of graphene (Gr), hBN shows many similar properties, including large specific surface area, high thermal conductivity, high wear resistance, superior impermeability property, good chemical inertness, and thermal stability . Due to the fascinating properties, to date, numerous studies have been reported related to BN-based composites to enhance the thermal conductivities, mechanical barrier, and thermal stability properties. It is well-known that Gr can trigger microgalvanic corrosion and potentially accelerate metal deterioration due to its highly electrical conductivity, which greatly limits the long-term application of Gr on metal protection. In contrast, hBN is an unconductive material . Therefore, hBN is particularly promising in metal protection fields.…”
Section: Introductionmentioning
confidence: 99%
“…As the structural analogue of graphene (Gr), hBN shows many similar properties, including large specific surface area, high thermal conductivity, high wear resistance, superior impermeability property, good chemical inertness, and thermal stability . Due to the fascinating properties, to date, numerous studies have been reported related to BN-based composites to enhance the thermal conductivities, mechanical barrier, and thermal stability properties. It is well-known that Gr can trigger microgalvanic corrosion and potentially accelerate metal deterioration due to its highly electrical conductivity, which greatly limits the long-term application of Gr on metal protection. In contrast, hBN is an unconductive material . Therefore, hBN is particularly promising in metal protection fields.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the roles of the conductive MXene and the galvanic corrosion mechanism during the failure process of coatings have not been explored. In previous work, 25–27 we have confirmed that parallelly arranged graphene nanosheets could inhibit the formation of conductive networks, and thus, eliminate the galvanic corrosion activity of the graphene-based composite coatings. Similarly, Wang et al 46,47 also found that the corrosion promotion activity could be restricted through orientating graphene nanosheets in the coatings.…”
Section: Resultsmentioning
confidence: 58%
“…As expected, the SZ of the OMC coating is much higher than that of most of the randomly distributed modified BN/EP 34–37 and G/EP 38–43 composite coatings. Interestingly, the SZ of the OMC coating is slightly lower than that of the self-aligned G/EP composite coatings, 25,26,44–47 which is mainly attributed to the inherently complete impermeability of graphene itself or the extra addition of corrosion inhibitors. Additionally, the F-graphene is becoming an attractive route to enhance the anticorrosion performance, 48 due to its superior antipermeation and adjustable conductivity.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the agglomeration of graphene sheets is minimized owing to the sequential formation of I-PDA-G-EP. The aligned layer structure agrees well with recent works. …”
Section: Results and Discussionmentioning
confidence: 99%